2012
DOI: 10.1128/jvi.00903-12
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Enters Rat Neuroblastoma Cells via a pH-Dependent, Dynamin and Caveola-Mediated Endocytosis Pathway

Abstract: bJapanese encephalitis virus (JEV) is a mosquito-borne flavivirus and one of the most common agents of viral encephalitis. The infectious entry process of JEV into host cells remains largely unknown. Here, we present a systemic study concerning the cellular entry mechanism of JEV to B104 rat neuroblastoma cells. It was observed that JEV internalization was inhibited by chloroquine and ammonium chloride, both of which can elevate the pH of acidic organelles. However, JEV entry was not affected by chlorpromazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 86 publications
(88 reference statements)
7
85
0
Order By: Relevance
“…Following pretreatment with 25 M chloroquine or 10 mM NH 4 Cl, viral RNA copy numbers of CSFV were reduced to 6.6% or 31.6% of those in untreated cells, whereas viral RNA copy numbers of JEV, another member of the Flaviviridae, used as a control, remained unchanged. In contrast, JEV infection was significantly inhibited by chloroquine or NH 4 Cl treatment in Vero cells (data not shown), consistent with data from a previous report (33). Taken together, the results indicated that CSFV infection required low-pH environments in the endosomes.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Following pretreatment with 25 M chloroquine or 10 mM NH 4 Cl, viral RNA copy numbers of CSFV were reduced to 6.6% or 31.6% of those in untreated cells, whereas viral RNA copy numbers of JEV, another member of the Flaviviridae, used as a control, remained unchanged. In contrast, JEV infection was significantly inhibited by chloroquine or NH 4 Cl treatment in Vero cells (data not shown), consistent with data from a previous report (33). Taken together, the results indicated that CSFV infection required low-pH environments in the endosomes.…”
Section: Resultssupporting
confidence: 82%
“…More than 70% inhibition of CSFV infection with 160 M dynasore was observed. Consistent with previously reported results (33), JEV infection was effectively blocked by dynasore treatment at 160 M (Fig. 2C).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations